Optimizing Ordering Policies for Imperfect Inventory Systems Integrating Trade Credit and Carbon Emission - Sahil Bhardwaj; Sudhir Kumar Chauhan; Mandeep Mittal; Leopoldo Eduardo Cárdenas-Barrón; Riju Chaudhary (International Journal of Mathematical, Engineering and Management Sciences)
Reducing carbon emissions is about protecting the future, in which the greatest treasures are clean air, a stable temperature and a thriving planet, not only about saving the environment. Using Hill's (1997) model, this study investigates how environmental factors might be included in inventory control—more especially, how trade credit, fuel prices, and pollution taxes might be used. This paper explores the continuous difficulty of keeping a regular supply of high-quality products in the dynamic market of today, where the possibility of providing faulty goods never disappears. This study aims primarily to minimise the predicted total cost by means of a derivative-based technique and to identify the ideal order quantity. These findings highlight a strong correlation between lowering carbon emissions and attaining financial savings. This paper emphasises the critical part environmental awareness plays in efficient inventory control. A sensible framework is presented for concurrently lowering prices and carbon emissions by including trade credit into Hill's (1997) model. A numerical example together with a sensitivity analysis shows the model's resilience. Finally, this study emphasises the need to include environmental elements into inventory control plans and provides a workable road to reach both environmental responsibility and financial economy.